HUBUNGAN ILMU AKHLAK DENGAN ILMU TAUHID - Darmansyah, Darmansyah (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2017)
Basically, there is a connection between every science whether the connection is tight, mediocre, or relatively far. Some subject that have a close connection with Ethical science are Tasawuf, Theology, Education Science, Psychiatry and Philosophy. Whereas, some science that have mediocre connection with Ethics are Law, Sosiology, History ad Anthropology. Some science that have far connection with Ethics are Physics, Biology and Politics.In this article, we will investigate the very close relationship between Ethics and Theology.